Effect of public housing redevelopment on reported and perceived crime in a Seattle neighborhood - Albertson, Elaine Michelle (Crime prevention and community safety, 2020)
Although research indicates that developing new public housing typically does not increase neighborhood crime, little is known about the impact of revitalizing existing public housing properties, also known as redevelopment. This study evaluates the effect of a multi-component physical and social redevelopment project on reports and perceptions of neighborhood crime in Seattle, Washington. We compare administrative police data with findings from a community survey to assess trends during early-to-mid redevelopment. While perceptions of safety improved over the study period, most crime-specific trends were not significantly different at the redevelopment site relative to comparison sites where no redevelopment occurred. Results suggest that this project did not have obvious adverse effects on crime rates. Although this redevelopment may have had a positive effect on perceptions of crime and safety in the short-term, it may take longer to realize beneficial effects on actual experiences or reports of crime.